2011
DOI: 10.22201/ib.20078706e.2011.2.471
|View full text |Cite
|
Sign up to set email alerts
|

Ciclo reproductor de Sceloporus ochoterenae en el estado de Morelos, México

Abstract: Se estudió el ciclo de reproducción de Sceloporus ochoterenae en una población que vive en un relicto de selva baja caducifolia en el centro de Morelos. Los machos con longitud hocico-cloaca (LHC) promedio de 49.53 ± 2.40 mm, son más grandes y más pesados (x = 3.66 ± 0.68 g) que las hembras (LHC 46.37 ± 2.08 mm, peso 3.34 ± 1.23 g), lo que revela dimorfismo sexual como ocurre en otras especies de lagartijas sceloporinas. Existen diferencias en los ciclos de reproducción entre los sexos, los machos inician la a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
(25 reference statements)
1
7
0
6
Order By: Relevance
“…Gonadal recrudescence of both sexes coincides with an increase in temperature, and reproductive activity extends until late summer, when temperature begins to decrease (Figure ). This pattern is shared with S. ochoterenae , the sister species of S. jalapae ( Wiens et al., ) that inhabits in a tropical deciduous forest (Bustos‐Zagal et al., ). However, the period of reproductive activity of S. ochoterenae is shorter than the one shown by S. jalapae , which suggests that several squamate life history traits are restricted by environment (Guillette & Méndez‐de la Cruz, ).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Gonadal recrudescence of both sexes coincides with an increase in temperature, and reproductive activity extends until late summer, when temperature begins to decrease (Figure ). This pattern is shared with S. ochoterenae , the sister species of S. jalapae ( Wiens et al., ) that inhabits in a tropical deciduous forest (Bustos‐Zagal et al., ). However, the period of reproductive activity of S. ochoterenae is shorter than the one shown by S. jalapae , which suggests that several squamate life history traits are restricted by environment (Guillette & Méndez‐de la Cruz, ).…”
Section: Discussionmentioning
confidence: 86%
“…However, all individuals born in a season could reproduce in the following spring. Early sexual maturity has been considered an exclusive characteristic of viviparous species within Sceloporus (Guillette & Méndez‐de la Cruz, ; Méndez‐de la Cruz et al., ), but individuals of several oviparous species of small size can also reproduce some months after birth (Bustos‐Zagal et al., ; Hernández‐Gallegos et al., , ; Manríquez‐Morán et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lengths and widths of the gonads were used to obtain testicular and follicular volume ( V ), which was calculated using the formula of an ellipsoid: V = (4/3) πa 2 b , where a is one‐half the shortest diameter and b is one‐half the longest diameter (Ramírez‐Bautista & Vitt, 76; Selby, 85). Testicular and follicular volumes were used as indicators of reproductive activity of both sexes (Bustos‐Zagal, Méndez‐de la Cruz, Castro‐Franco, & Villagrán‐Santa Cruz, 6; Hernández‐Salinas et al, 30; Ramírez‐Bautista et al, 71; Ramírez‐Pinilla, Calderón‐Espinosa, Flores‐Villela, Muñoz‐Alonso, & Méndez‐de La Cruz, 77).…”
Section: Methodsmentioning
confidence: 99%
“…Although there have been several studies on reproductive cycles in oviparous species within different environments, in general, it has been determined that the reproductive activity of oviparous species in temperate areas is seasonal and is restricted to spring and summer. It is the most common pattern where reproductive events between both sexes occur synchronously (Bustos‐Zagal, Méndez‐de la Cruz, Castro‐Franco, & Villagrán‐Santa Cruz, 2011; Fitch, 1970; Goldberg, 2014; Guillette & Méndez‐de la Cruz, 1993; Hernández‐Gallegos et al., 2014; Méndez‐de la Cruz, Villagrán‐Santa Cruz, López‐Ortíz, & Hernández‐Gallegos, 2013; Villagrán‐Santa Cruz et al, 2009). However, a few recent studies have shown that there is variation in the time, duration and intensity of the different gametogenic phases (see Granados‐González et al., 2015, 2017).…”
Section: Introductionmentioning
confidence: 99%